Konsumen Dan Iklan: Perlindungan Konsumen Dalam Penyiaran Iklan yang Menyesatkan Di Radio - Krisanti, Hana; Wardiono, kelik (JUSTISI, 2023)
This research which is based on a doctrinal approach aims to describe consumer protection in broadcasting advertisements on 3 radio channels in Surakarta. The data used is secondary data in the form of advertisements broadcast through radio electronic media obtained through library research. Based on the results of the research and discussion conducted, it is known that consumers have not been protected from advertisements broadcast on the radio, this is because there are still many advertisements that are contrary to applicable laws and regulations, such as using excessive words, price inclusion, wrong information/ imprecise, warranty/guarantee, disparaging, information overload